2014
DOI: 10.1038/cddis.2014.487
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of A1 and A2B adenosine receptor activity: a new strategy to sensitise glioblastoma stem cells to chemotherapy

Abstract: Therapies that target the signal transduction and biological characteristics of cancer stem cells (CSCs) are innovative strategies that are used in combination with conventional chemotherapy and radiotherapy to effectively reduce the recurrence and significantly improve the treatment of glioblastoma multiforme (GBM). The two main strategies that are currently being exploited to eradicate CSCs are (a) chemotherapeutic regimens that specifically drive CSCs toward cell death and (b) those that promote the differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
88
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(98 citation statements)
references
References 64 publications
9
88
1
Order By: Relevance
“…Previous studies have indicated that the activation of A1R may be associated with the ERK/JNK pathway. A1R agonist induced the phosphorylation of ERK/JNK, while its antagonist could inhibit the phosphorylation [19, 28, 29]. Our results are consistent with these previously published reports, suggesting that DPCPX may inhibit tumor progression in part via the ERK/JNK pathway (Fig.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Previous studies have indicated that the activation of A1R may be associated with the ERK/JNK pathway. A1R agonist induced the phosphorylation of ERK/JNK, while its antagonist could inhibit the phosphorylation [19, 28, 29]. Our results are consistent with these previously published reports, suggesting that DPCPX may inhibit tumor progression in part via the ERK/JNK pathway (Fig.…”
Section: Discussionsupporting
confidence: 83%
“…In contrast, several studies also showed that the A1R antagonists could reduce cell proliferation [13, 18]. Notably, a combined treatment with A1R agonist and temozolomide significantly inhibited cell proliferation and promoted apoptosis compared to temozolomide alone in cancer stem cells [19], whereas A1R antagonist DPCPX was found to significantly induce apoptosis in MCF-7 cells [18]. In this study, the expression of A1R was up-regulated; thus, the A1R antagonist DPCPX was used.…”
Section: Discussionmentioning
confidence: 99%
“…A 1 R activation inhibits proliferation in human metastatic cell line, and A 2A R activation promotes human melanoma cell death [50,51]. AdoR activation also has been shown to sensitize glioma cells to chemotherapic cytotoxic effects [52,53]. In this way, it has been already described that AdoR activation is capable of modulating apoptotic pathways in colorectal cancer, hepatocellular carcinoma, osteosarcoma, and lung cancer, for example, increasing BAX and BAD levels, promoting alteration in mitochondrial membrane potential and increasing the efflux of cytochrome C and triggering apoptosis [45].…”
Section: Discussionmentioning
confidence: 99%
“…Noteworthy, adenosine, resulting from ATP hydrolysis by the ectoenzymes CD73 and CD39 exerts effect that are often opposite to those of ATP (see details in previous section), such as the promotion of an immunosuppressive environment via A2A receptors 76, 116, 117 as well as chemotaxis and metastasis via A2B receptors 79 . However, adenosine can also induce tumor cell death, via A1, A2A, A2B and A3 receptors 19118 , thereby additionally contributing to limit tumor growth (Fig 2). Therefore, the kinetics of ATP release and conversion to adenosine, as well as the large number of receptors for ATP and adenosine need to be taken into consideration when targeting this system for ICD induction.…”
Section: Contribution Of Damps To Tumor Inhibition/rejection Via Imentioning
confidence: 99%